Frequency of Diarrhoea and its Risk Factors among Children Under-Five Years of Age in Three Teaching Hospitals of Peshawar - Nighat Musa; Riaz Gul; Yasir Mehmood; Shazma (Gandhara University, 2016)
OBJECTIVE: To determine the frequency of diarrhea and its risk factors among children under-five years of age. METHODOLOGY: Study design was descriptive observational. Duration of the study was three months (Jan - March 2014). Study was conducted in three tertiary hospitals of Peshawar namely Lady reading hospital, Khyber teaching hospital & Hayatabad Medical Complex. MATERIALS AND METHODS: Sample size for this study was calculated based on diarrhea prevalence of 21% in Peshawar by using WHO sample size calculator. A total of 450 children under 5 years of age who were attending outpatient department of three tertiary hospitals of Peshawar were studied. After getting consent from parents of children, data was collected from parents. A semi structured questionnaire was used as study tool. Data was presented in the form of tables and graphs. RESULTS: Frequency of diarrhea was found to be 59% among those 450 children who attended pediatric OPD. Most susceptible age group was less than 2 years (88%). Common risk factors found to be involved in cases of diarrhea were illiteracy of mothers 77%, poverty 86.4% parents were having household income less than 20,000 PKR per month, bottle feeding 34%, improper hygiene (83% either don't wash or occasionally wash hands before feed, 52.3% mothers wash their hands with plain water after attending toilet), Joint families 58%, lack of proper immunization 54%, lack of clean drinking water 66%. CONCLUSIONS: Diarrhea is more common in younger children i.e.; less than 2 years of age. Illiteracy, low household income, bottle feeding, hand washing especially after attending toilet, joint family system and poor immunization status are the key risk factors.